2010
DOI: 10.1002/jhbs.20468
|View full text |Cite
|
Sign up to set email alerts
|

The science of ethics: Deception, the resilient self, and the APA code of ethics, 1966–1973

Abstract: This paper has two aims. The first is to shed light on a remarkable archival source, namely survey responses from thousands of American psychologists during the 1960s in which they described their contemporary research practices and discussed whether the practices were "ethical." The second aim is to examine the process through which the American Psychological Association (APA) used these survey responses to create principles on how psychologists should treat human subjects. The paper focuses on debates over w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 58 publications
0
56
0
Order By: Relevance
“…Thus, the University of Manitoba established a four‐person committee to oversee Zubek's use of experimental subjects, a move that was beyond what was expected at Canadian universities at the time. Furthermore, Zubek had spent prolonged periods of time in the sensory deprivation chamber himself, and certainly did not consider his work as research on torture or interrogation (H. H. Saunderson, President of the University of Manitoba, letter to Jeanne L. Bran, NIMH, April 26, 1966, Box 6 Folder 15; Swift, Macleod, Deacon, Kirby and Gregory, Barristers & Solicitors Firm, to W. J. Condo, Vice President of the University of Manitoba, May 11, 1966, Box 6, Folder 14, JZ Collection, UMA; Stark, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the University of Manitoba established a four‐person committee to oversee Zubek's use of experimental subjects, a move that was beyond what was expected at Canadian universities at the time. Furthermore, Zubek had spent prolonged periods of time in the sensory deprivation chamber himself, and certainly did not consider his work as research on torture or interrogation (H. H. Saunderson, President of the University of Manitoba, letter to Jeanne L. Bran, NIMH, April 26, 1966, Box 6 Folder 15; Swift, Macleod, Deacon, Kirby and Gregory, Barristers & Solicitors Firm, to W. J. Condo, Vice President of the University of Manitoba, May 11, 1966, Box 6, Folder 14, JZ Collection, UMA; Stark, ).…”
Section: Resultsmentioning
confidence: 99%
“…These debates culminated in the 1973 publication of Ethical Principles in the Conduct of Research with Human Participants , a booklet prepared by a commission of experts, which was incorporated into the American Psychological Association's code of ethics (Ethical Principles, ). Laura Stark has analyzed the extensive debate over what forms of deception were ethically acceptable, a deliberation which was couched in contemporary concepts of the meaning of selfhood (Stark, , pp. 359–68).…”
Section: Resultsmentioning
confidence: 99%
“…Bioethics is no longer viewed simply as a set of abstract principles and guidelines implemented to reproduce the legitimacy and authority of medical professionals (Kleinman, 1996(Kleinman, , 1999Rosenberg, 1999;Timmermans and Berg, 2003). In examining the relation between personal experience and formalised ethics, authors have demonstrated the various ways in which bioethics influences and is played out in vis-à-vis specific economic, political, and medic-scientific scenarios (Petryna, 2002(Petryna, , 2005(Petryna, , 2009Brodwin, 2005Brodwin, , 2008Brodwin, , 2012Jasanoff, 2005;Stark, 2010). Ethical regulation varies between local contexts in relation to specific economic and political circumstances, while ethical deliberation often takes on the characteristics and concerns of the (nation) State in which it is taking place (Jasanoff, 2005;Petryna, 2005Petryna, , 2009Sperling, 2007).…”
Section: Coproduction Imaginaries and (Bio)ethicsmentioning
confidence: 98%
“…Some research disciplines have adopted an ethics charter or specific deontology code: in addition to doctors, this includes some archaeologists, psychologists (https://www.apa.org/ethics/code/ethics-code-2017.pdf), sociologists (code of the American Sociological Association), historians (https://apps.carleton.edu/curricular/history/resources/study/ahaEthicalPractices/) and anthropologists (ethics charter of the AAA -American Anthropological Association). These charters sparked debates and were sometimes abandoned (El Miri and Masson 2009;Stark, 2010); all the members of a discipline did not adhere to it. In short, France practises -albeit late -the regulatory stack that others have long criticised as misregulation, in the name of counterproductive moralisation practised by scientists themselves (in Canada, Trudel and Jean, 2010;Doucet, 2010;in the United States, Bonnet Robert, 2009).…”
Section: Multiplying Regulationsmentioning
confidence: 99%